2020
DOI: 10.21203/rs.3.rs-61545/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Interleukin-7 loaded oncolytic adenovirus improves CAR-T cell therapy for glioblastoma

Abstract: Background: T cell with chimeric antigen receptors (CAR-T) has presented remarkable efficacy for blood cancer as an emerging immunotherapy. However, for solid tumors, the therapeutic efficacy is much impaired due to the lack of infiltration and persistence of CAR-T in tumor tissue. Thus, we constructed an interleukin-7-loaded oncolytic adenovirus and combined the use of oncolytic virus and CAR-T to improve the therapeutic outcome.Methods: We constructed an interleukin-7 loaded oncolytic adenovirus (oAD-IL7) an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…Huang et al also developed an oncolytic adenovirus containing IL7 and integrated it with B7H3-targeting CAR-T cells to investigate its efficiency in treating glioblastoma. They found that the combined use of them presents synergistic antitumor impact in vitro and in vivo by supporting T cell persistence, resulting in longer survival of tumor-bearing mice [122].…”
Section: Oncolytic Virotherapy In Combination With Car-t Cellmentioning
confidence: 99%
“…Huang et al also developed an oncolytic adenovirus containing IL7 and integrated it with B7H3-targeting CAR-T cells to investigate its efficiency in treating glioblastoma. They found that the combined use of them presents synergistic antitumor impact in vitro and in vivo by supporting T cell persistence, resulting in longer survival of tumor-bearing mice [122].…”
Section: Oncolytic Virotherapy In Combination With Car-t Cellmentioning
confidence: 99%